Dietary Intake and Nutritional Status in Diabetic and Nondiabetic Patients With Chronic Kidney Disease Stage 4-5 (NutriDiab Study) - Oliveira, Mariana Cassani [UNESP]; Viney, Angelique; Picard, Elodie; Barnel, Cécile; Fouque, Denis; Koppe, Laetitia (Elsevier, 2024)
Objectives: The aim of the present study was to assess the dietary intake and nutritional status of patients with chronic kidney disease (CKD) stage 4-5 according to the presence of diabetes. Methods: This observational and cross-sectional study included adult patients with CKD stage 4-5 referred to a nephrology unit, between October 2018 and March 2019. Daily dietary intake was evaluated by 24-hour dietary inquiry and urine excretion. Nutritional status was assessed by measuring body composition using bioimpedance analysis and muscle function using handgrip strength. Undernutrition was considered using the protein energy wasting score. Results: A total of 75 CKD patients were included, 36 (48%) of whom had diabetes; median age (interquartile range) was 71 (60-80) years. The median weight-adjusted dietary energy intake (DEI) was 22.6 (19.1-28.2) kcal/kg/day and the mean weight-adjusted dietary protein intake (DPI) was 0.86 ± 0.19 g/kg/day. There was no significant difference in DEI and DPI between patients with diabetes and those without, except for weight-adjusted DPI which was significantly lower in diabetic patients (P =.022). In univariate analysis, diabetes was associated with weight-adjusted DPI (coefficient [95% confidence interval] −0.237 [-0.446; −0.004] kcal/kg/day; P =.040), but this association did not remain significant in multivariate analysis. Nutritional status did not differ significantly between diabetic and nondiabetic patients except for lean tissue mass, which was lower in diabetic patients (P =.046). The proportion of patients with protein energy wasting was not significantly different between diabetic and nondiabetic patients (13.9% vs. 10.2%, respectively). Conclusions: In the present cohort, DPI and DEI were not significantly different between diabetic and nondiabetic CKD patients. Diabetes was not found to be associated with dietary intakes in CKD stage 4-5 patients.
Keywords: Chronic kidney disease; Diabetics; Nutrition; Protein energy-wasting; Protein intake